Novel methodology to replicate clot analogs with diverse composition in acute ischemic stroke. (28th April 2016) - Duffy, Sharon; Farrell, Michael; McArdle, Kevin; Thornton, John; Vale, David; Rainsford, Eleanor; Morris, Liam; Liebeskind, David S; MacCarthy, Eugene; Gilvarry, Michael
Abstract : Background: Translational research on clot composition may be advanced by the use of clot analogs for the preclinical evaluation of mechanical thrombectomy devices. This work describes a novel set of clot analogs to represent a diverse range of fibrin and red blood cell (RBC) compositions for use in acute ischemic stroke (AIS) occlusion models. Method: Fresh whole blood obtained from ovine species was used to create seven different clot analog types. Five replicates were formed for each clot type. Varying amounts of whole blood constituents were mixed with thrombotic factors to create clots of varying compositions. Following histological processing, five sections from each clot were stained with H&E and Martius Scarlet Blue. Fibrin, RBC and white blood cell compositions were quantified. Results: Histological examination demonstrated that the clot types had a distinct RBC and fibrin composition. No significant difference in composition was shown between replicates (p>0.05), indicating that the method of clot formation was reproducible. Percentage fibrin composition of the clot types was 1%, 8%, 31%, 38%, 64%, 79%, and 100%. A significant difference in fibrin and RBC composition between clot types was observed (p<0.05). Conclusions: Seven different clot types were developed to replicate common AIS thrombi. These clot analogs may be beneficial for the preclinical evaluation of endovascular therapies, and may be applied to interventional technique training.